SURGICAL TREATMENT OF MACROSTOMIA IN LATERAL FACIAL CLEFTS - Okur, M. Ihsan; Kose, Rustu; Yildirim, A. Mustafa (Medknow Publications & Media Pvt Ltd, 2009)
Rare facial clefts are classified by Tessier. Our purpose is to discuss planning of the surgical treatment of lateral facial clefts that is described as No. 7 cleft in this classification and evaluate the results. The laterally stretched orbicularis oris muscles of three patients who had lateral facial cleft were repaired in the ring form. A Z plasty was made at the nasolabial sulcus level during the closure of the skin. There were macrostomia due to facial cleft in three patients. Preauricular accessory cartilages existed in one of them. However, none of the patient had a major external auricular anomaly. The outcomes of the macrostomia surgery was successful. The symmetry of the mouth was acceptable when it was open and closed. By anatomical repair of the orbicularis oris muscle and avoiding straight line skin repair, desired results can be achieved in the surgical treatment of the lateral facial clefts.
Keywords: lateral facial cleft; Tessier no. 7 cleft; transvers facial clefts; rare facial clefts; surgical technique